EFISIENSI USAHATANI BUNGA KRISAN (Chrysantemum indicum) DI KECAMATAN KANDANGAN KABUPATEN TEMANGGUNG - Puspita, Nurul; Khamdi, Ali (Universitas Muhammadiyah Semarang, 2022)
Chrysanthemum flowers in Indonesia had the highest production rate among other types of cut flowers in 2021-2022. One of the things that needs to be considered in the chrysanthemum farming is production fluctuations that can affect farmers' income. This study aims to: (1) knowing the size and cost of farming income of chrysanthemum farmers in Kandangan District; (2) knowing the value of farming efficiency; and (3) determine the effect of social and economic factors on the income of chrysanthemum farmers. The research location was determined purposively with the consideration that Kandangan Subdistrict is the highest area of chrysanthemum production in Temanggung Regency. The research respondents were selected using the Non Probability Sampling technique, namely census. Data analysis methods used include: (1) analysis of costs and revenues; (2) efficiency analysis; and (3) multiple regression models with the profit function approach. The results showed the average cost of chrysanthemum flower farming in Kandangan Subdistrict is Rp. 125.770.282,42 / Ha, the average amount of revenue is Rp. 265.051.401,87 / Ha, so that the average income earned is Rp. 139.281.119,45 / Ha. The efficiency of chrysanthemum farming is 2,01, which means that every cost of Rp. 1,00 issued by farmers will generate revenue of Rp. 2,01 so that the chrysanthemum farming in Kandangan Subdistrict has been efficient and profitable, so it is worth cultivating.